PENYELESAIAN SENGKETA TANAH DI JALAN WOLTER MONGONSIDI SAMARINDA ( ANALISIS PENETAPAN PUTUSAN PENGADILAN NEGERI SAMARINDA NOMOR: 101/Pdt.G/2013/PN.SAMARINDA ) - Agustina Evie (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThe purpose of this study was to find solution to the problem of land disputes rife in the country. As we all know the problem of land ownership always arise from time to time. In this case I chose  land dispute case in road Walter Mongonsidi where plaintiff purchased the land on the basis of letter of waiver but it is known that the certificate has been published in the National Land Agency of the Land.This study used data collecyion techniques by reading, studying and digging through the staff at the District Court of Samarinda, interviews with plaintiffs and attend proceedings dirrectly in the casa of land dispute resolution Wolter Mongonsidi Road. The nature of this study is qualitative descriptive analysis that describes the theory of civil law with the realities of legal practise in the field, as well as the impact of a slight difference from theories to practice.The result showed was a consideration in decidingcase judges not only revolve around the legal principle of justice, moral justice and social justice, but on the conscience, so that the law really be justice in the hands of judges and powerless function for justice seekers.Keywords : land dispute